Monitoring and understanding chlorophyll-a concentration changes in lakes in northeastern China using MERIS and OLCI satellite data - Lu Zhang; Zhuohang Xin; Qi Guan; Lian Feng; Chuanmin Hu; Chi Zhang; Huicheng Zhou (GIScience & Remote Sensing)
Lakes in the Northeast Plains-Mountain Lake Region (NPLR) of China face severe risks of eutrophication due to climate change and intensive anthropogenic pressures. As a vital indicator for eutrophication status, the dynamics of chlorophyll-a (Chl-a) concentrations in NPLR lakes were, for the first time, comprehensively investigated in this study. A support vector regression (SVR)-based model was established and applied to the MERIS (2003–2011) and OLCI (2016–2019) observations to derive a long-term Chl-a record for 33 NPLR lakes. The NPLR lakes exhibited a climatological annual mean Chl-a of 12.3 mg m−3, ranging from 6.8 to 18.6 mg m−3 among the 33 studied lakes. During the study period, 11 lakes exhibited statistically significant increases in Chl-a concentrations (p < 0.05), and 3 lakes showed significantly decreasing trends. Spatially, lakes in lowland regions had higher Chl-a than those in mountainous regions. This study quantified the relative importance of seven explanatory factors in influencing interannual Chl-a changes for each lake. Results showed statistically significant impacts of agricultural fertilizer (10 lakes), wastewater (4 lakes), runoff (7 lakes), and wind (5 lakes) in affecting the interannual variations of Chl-a. The decreases in Chl-a were primarily attributed to the reduced livestock excrement. Compared to hydro-climatic factors, anthropogenic pressures (i.e. agriculture fertilizer, livestock excrement, and wastewater discharge) had more significant impacts on the interannual variations of Chl-a, accounting for more than 50% of 18 lakes. This study enhances our understanding of the long-term Chl-a dynamics in NPLR lakes and their responses to hydro-climatic factors and anthropogenic forcing. These findings are valuable for basin-scale water environment protection and sustainable development.